Franchise Protection Law to Secure Rights and Obligations in Joint Business - Christian, Benedict Philip (CV. Rayyan Dwi Bharata, 2023)
Franchise business (franchise) is a business system that is currently favored by many people. From the franchise system, doing business becomes easier, because franchising is the right of each entrepreneur or business entity to market goods or services that are proven by the running of a